Dekonstruksi Hijab (Kajian Sosio-Historis terhadap Konstruksi Hukum Hijab dalam Islam) - Nuroniyah, Wardah (Fakultas Syariah IAIN Purwokerto, 2017)
Hijab has always been a controversial issue. Some Muslims consider it a mandatory command of God, while others consider it a cultural practice that can change so that the law is not the wearing of hijab itself. This paper examines the meaning of hijab in the Qur'an by using a mechanism commonly referred to as double investigations / double movement, i.e. by examining the context of the first time the hijab was revealed, to whom and how was the social construct of the hijab when the verses of hijab was firstly enforced. The next investigation is the semantic meaning contained in the hijab rhetoric and its sociological implications. In terms of the methodology for this study of hijab, the authors perform a falsification test to find out whether the hijab concept that has existed is still relevant to present reality or not, and to seek the truth that is adapted to the present reality. This paper concludes that the Qur'anic teaching on hijab can adapt to the context of a modern woman as smoothly as it adapted to the early Muslim community 14 centuries ago. This adaptation can be proven if the Qur'anic texts are interpreted by taking into account the social context of Muslim societies with their social changes.